"Necessary evil": the difficulties of establishing programmatic culture in the transfer portal era - Chris Corr; Trevor Bopp; Sarah Stokowski (Frontiers Media S.A., 2024)
The implementation of the transfer portal and eased transfer restrictions has drastically impacted the migration of college football players. While such athlete autonomy aligns with sweeping organizational policy adopted, and mandated, by the National Collegiate Athletic Association (NCAA), the absence of barriers preventing the mobility of players may have a resultant effect on the development of sustained organizational culture. Through interviews with direct stakeholders currently coaching football at the Football Bowl Subdivision (FBS) level, the findings of this study reveal that while the transfer portal is commonly utilized to achieve short-term success, building a roster composed predominantly of transfer players was perceived as unsustainable in the desired cultivation of meaningful organizational culture. As coaches grapple with the intensified demands to win football games, the findings of this study indicate that sustained long-term programmatic success may be more suitably achieved through the cultivation of distinct organizational culture rather than a reliance on transfer players.